Calcium hydroxide dressing residues after different removal techniques affect the accuracy of Root-ZX apex locator - Emel Uzunoglu; Ayhan Eymirli; Mehmet Özgür Uyanik; Semra Çalt; Emre Nagas (Korean Academy of Conservative Dentistry, 2015)
Objectives This study compared the ability of several techniques to remove calcium hydroxide (CH) from the root canal and determined the influence of CH residues on the accuracy of the electronic apex locator. Materials and Methods Root canals of 90 human maxillary lateral incisors with confirmed true working length (TWL) were prepared and filled with CH. The teeth were randomly assigned to one of the experimental groups according to the CH removal technique (n = 14): 0.9% saline; 0.9% saline + master apical file (MAF); 17% ethylenediamine tetraacetic acid (EDTA); 17% EDTA + MAF; 5.25% sodium hypochlorite (NaOCl); 5.25% NaOCl + MAF. Six teeth were used as negative control. After CH removal, the electronic working length was measured using Root-ZX (Morita Corp.) and compared with TWL to evaluate Root-ZX accuracy. All specimens were sectioned longitudinally, and the area of remaining CH (CH) and total canal area were measured using imaging software. Results The EDTA + MAF and NaOCl + MAF groups showed better CH removal than other groups (p < 0.05). Root-ZX reliability to prevent overestimated working length to be > 85% within a tolerance of ± 1.0 mm (p < 0.05). There was strong negative correlation between amount of CH residues and EAL accuracy (r = -0.800 for ± 0.5 mm; r = -0.940 for ± 1.0 mm). Conclusions The mechanical instrumentation improves the CH removal of irrigation solutions although none of the techniques removed the dressing completely. Residues of CH medication in root canals affected the accuracy of Root-ZX adversely.